(untitled) (Bangladesh Journal of Pharmacology, 2021)
The present study was undertaken to decipher the role of HOXC10 gene in regulating the growth and metastasis of prostate cancer. The results revealed significant (p<0.05) up-regulation of HOXC10 gene in human prostate cancer tissues and cell lines. The silencing of HOXC10 transcript level significantly (p<0.05) inhibited the growth and colony formation of DU145 and 22Rv1 prostate cancer cells. The DAPI staining revealed that inhibition of DU145 and 22Rv1 prostate cancer cell viability was due to the induction of apoptosis. The transwell assay showed that HOXC10 significantly (p<0.05) inhibits the invasion of prostate cancer cells. The Western blotting revealed that HOXC10 gene exerts its effects via modulation of Ras/Raf/MEK/ERK signaling cascade. Collectively, the results point towards the therapeutic potential of HOXC10 in the treatment of prostate cancer.